Reaction of rat connective tissue to a new calcium hydroxide-based sealer - Gomes Filho, João Eduardo [UNESP]; Bernabé, Pedro Felício Estrada [UNESP]; Nery, Mauro Juvenal [UNESP]; Otoboni Filho, José Arlindo [UNESP]; Dezan Junior, Eloi [UNESP]; Teixeira de Moraes Costa, Mariana Machado [UNESP]; de Faria, Max Douglas [UNESP]; Watanabe, Simone [UNESP]; Gomes, Alessandra Cristina [UNESP] (Mosby-elsevier, 2008)
The aim of this study was to histopathologically examine the reaction of the connective tissue of rats to 2 calcium hydroxide-based sealers, Acroseal and Sealapex. Dentin tubes containing the materials and empty control tubes were implanted into the dorsal connective tissue of 36 Wistar albino rats. The animals were killed after 7 or 30 days, and the specimens were prepared for histologic analysis with hematoxylin and eosin, Von Kossa technique, and polarized light. Results were statistically analyzed using Kruskal-Wallis test. Both materials caused mild or moderate inflammatory reactions on the 7th day, but these reactions decreased by the 30th day with no significant difference at any time (P > .05). Mineralization of the subcutaneous tissue of the rats was observed only with Sealapex.